Utility of Piperine and Liquisolid Tablets to Enhance the Pharmacological Profile of Tacrolimus - Ali, Ahmed S.; Oumar, I. H.; Ahmed, O. A. A.; El-Say, K. M.; Alsieni, M.; Alkreathy, H. M. (Journal of Contemporary Medical Sciences, 2025)
Objective: To evaluate the impact of a self-nanoemulsifying drug delivery system (SNEDDS) incorporated into liquisolid tablets (LSTs) and the natural bioenhancer piperine (Pip) on the bioavailability, immunosuppressive efficacy, and toxicity of tacrolimus (Tac). Methods: An optimized Tac-SNEDDS was developed and formulated into four LST compositions using various carriers and coatings (Neusilin®-Avicel®/FujiSil®-fumed silica). The optimal Tac-LST formulation was selected based on drug content and tested in Wistar rats. Bioavailability was assessed using the limited area under the curve (AUC₀₋₆), while immunosuppressive efficacy was evaluated through IL-2 levels. Renal histology and serum cystatin C levels were analyzed to assess potential nephrotoxicity. Results: Among the four Tac-LST formulations, LST-4 (Avicel®/FujiSil®) exhibited the highest drug content and was chosen for in vivo studies. Co-administration of Pip, LSTs, and their combination significantly improved Tac bioavailability without compromising immunosuppressive activity. Pip co-administration demonstrated superior IL-2 inhibition compared to Tac alone or Tac-LSTs. Additionally, Pip reduced Tac-induced increases in serum cystatin C levels and mitigated renal histological damage, indicating a nephroprotective effect. The combination of Pip and Tac-LSTs provided the most stable absorption profile with minimal AUC fluctuations, suggesting a more predictable pharmacokinetic profile. Conclusion: Pip and LST formulations significantly enhance Tac bioavailability while maintaining its immunosuppressive efficacy. Moreover, Pip exhibits a protective effect against Tac-induced nephrotoxicity. The combination of Pip and Tac-LSTs offers a stable pharmacokinetic profile, potentially improving therapeutic outcomes by maintaining consistent drug levels.